Origin and phylogenetic relationships of [4Fe–4S]‐containing O2 sensors of bacteria. (5th October 2018) - Barth, C.; Weiss, M. C.; Roettger, M.; Martin, W. F.; Unden, G.
Summary: The advent of environmental O2 about 2.5 billion years ago forced microbes to metabolically adapt and to develop mechanisms for O2 sensing. Sensing of O2 by [4Fe–4S] 2+ to [2Fe–2S] 2+ cluster conversion represents an ancient mechanism that is used by FNREc ( Escherichia coli ), FNRBs ( Bacillus subtilis ), NreBSa ( Staphylococcus aureus ) and WhiB3Mt ( Mycobacterium tuberculosis ). The phylogenetic relationship of these sensors was investigated. FNREc homologues are restricted to the proteobacteria and a few representatives from other phyla. Homologues of FNRBs and NreBSa are located within the bacilli, of WhiB3 within the actinobacteria. Archaea contain no homologues. The data reveal no similarity between the FNREc, FNRBs, NreBSa and WhiB3 sensor families on the sequence and structural levels. These O2 sensor families arose independently in phyla that were already present at the time O2 appeared, their members were subsequently distributed by lateral gene transfer. The chemistry of [4Fe–4S] and [2Fe–2S] cluster formation and interconversion appears to be shared by the sensor protein families. The type of signal output is, however, family specific. The homologues of FNREc and NreBSa vary with regard to the number of Cys residues that coordinate the cluster. It is suggested that the variants derive from lateral gene transfer and gained other functions.